Kesehatan Kerja Tenaga Perpustakaan dalam Perspektif Ergonomi: Studi Kasus Keluhan Muskuloskeletal di Perpustakaan - Hana Isnaini Al Husna; Fery Luvita Sari; Agus Taufiqurrohman (Universitas Sebelas Maret Library, 2025)
The library is a professional work environment where library personnel are engaged in static and repetitive activities, which pose a risk of musculoskeletal disorders (MSDs) that can affect staff well-being and service quality. This study addresses the issue of occupational health among library staff from an ergonomic perspective, focusing on the risk of musculoskeletal complaints resulting from static workloads and suboptimal working postures. The study aims to describe the characteristics of library personnel at the Islamic University of Indonesia (UII) Library, identify the level of MSD complaints, analyze the relationship between ergonomic risk factors (sitting duration, working hours, and body mass index) and MSDs, and examine the implications for human resource management policies in libraries to improve information service quality. Using a descriptive quantitative approach, a case study method, and the Nordic Body Map questionnaire administered to 32 library staff, data were analyzed using Spearman correlation tests. The results show that working hours (p=0.009; r=0.456), sitting duration (p=0.044; r=0.359), and body mass index (p=0.043; r=0.360) have significant correlations with MSD complaints, which are most commonly reported in the upper neck, lower back, and right shoulder areas. These findings highlight the urgency for library management to integrate ergonomic principles into human resource management policies, including workspace design, task scheduling, and occupational health programs. Optimizing the physical health of library personnel not only helps reduce MSDs but also enhances productivity, job satisfaction, and the overall quality of information services in modern libraries.